Negative modulation of NMDA receptor channel function by DREAM/calsenilin/KChIP3 provides neuroprotection? - Wang, Kewei; Wang, Yun (Frontiers in Molecular Neuroscience, 2012)
N-methyl D-aspartate receptors (NMDARs) are glutamate-gated ion channels highly permeable to calcium and essential to excitatory neurotransmission. The NMDARs have attracted much attention because of their role in synaptic plasticity and excitotoxicity. Evidence has recently accumulated that NMDARs are negatively regulated by intracellular calcium binding proteins. The calcium-dependent suppression of NMDAR function serves as a feedback mechanism capable of regulating subsequent Ca2+ entry into the postsynaptic cell, and may offer an alternative approach to treating NMDAR-mediated excitotoxic injury. This short review summarizes the recent progress made in understanding the negative modulation of NMDAR function by DREAM/calsenilin/KChIP3, a neuronal calcium sensor protein.